2016
DOI: 10.1111/clr.12905
|View full text |Cite
|
Sign up to set email alerts
|

Healing at implants placed in bone of different morphology: an experimental study in dogs

Abstract: Similar implant bed preparations performed at premolar and molar sites with different bone morphology, yielding insertion torque values of about 30-35 and 50-55 Ncm, respectively, did not affect osseointegration after 4 months at non-submerged implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…These results support the preclinical evidence of the good osteoproperties of OGI surface by Caroprese et al [ 32 ] that analysed in the osseointegration of implants with OGI surface installed using a standard bed preparation in sites of different bone morphology. Results confirmed that the final insertion torque was 50–55 Ncm at the premolar and 30–35 Ncm at the molar sites.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results support the preclinical evidence of the good osteoproperties of OGI surface by Caroprese et al [ 32 ] that analysed in the osseointegration of implants with OGI surface installed using a standard bed preparation in sites of different bone morphology. Results confirmed that the final insertion torque was 50–55 Ncm at the premolar and 30–35 Ncm at the molar sites.…”
Section: Discussionsupporting
confidence: 90%
“…This could reduce biocompatibility. However, OGI Titanium (Ti) surface microarchitecture has been shown to increase osteoblast differentiation [ 28 , 29 , 30 , 31 , 32 ] by our previous publication.…”
Section: Discussionmentioning
confidence: 99%
“…Implant primary stability is a key factor in achieving osseointegration and is one of the prerequisites for successful immediate/early loading procedures. 1 Primary stability is affected by multiple factors such as bone quality, 2 bone density, 3 bone morphology, 4 implant design, 5 implant surface roughness, 6 preparation of the implant site, [5][6][7][8] crestal bone anchorage, 9 apical anchorage through the cortical floor of the sinus or nasal cavities, 10 lateral cortical anchorage, 11 and implant dimensions. 2,12,13 Optimal implant stability is more difficult to achieve in lowdensity bone, such as that of the posterior maxilla.…”
mentioning
confidence: 99%